2013
DOI: 10.11564/27-1-5
|View full text |Cite
|
Sign up to set email alerts
|

New trends in under-five mortality determinants and their effects on child survival in Nigeria: A review of childhood mortality data from 1990-2008

Abstract: Under-five mortality in Nigeria has been reported to be on the decline, but the dynamics are yet to receive adequate attention. Thus the main objective of this study was to assess these factors and quantify their relative contributions to under-five mortality between 1990. The Nigeria Demographic and Health Survey data for 1990, 2003

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
54
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 51 publications
4
54
0
Order By: Relevance
“…Studies have revealed lower utilization of health facilities among pregnant women as an important determinant of infant mortality [14–16]. An infant mortality differential also exists according to place of residence, child’s sex, mother’s level of education and household wealth [17]. Others include number of antenatal visits, presence of a birth attendant, birth size and exclusive breastfeeding [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies have revealed lower utilization of health facilities among pregnant women as an important determinant of infant mortality [14–16]. An infant mortality differential also exists according to place of residence, child’s sex, mother’s level of education and household wealth [17]. Others include number of antenatal visits, presence of a birth attendant, birth size and exclusive breastfeeding [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…An infant mortality differential also exists according to place of residence, child’s sex, mother’s level of education and household wealth [17]. Others include number of antenatal visits, presence of a birth attendant, birth size and exclusive breastfeeding [17,18]. Findings from scientific studies have also established a strong relationship between infant mortality and specific demographic factors like maternal age at childbirth, birth order and preceding birth interval [18].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations